Case study based model to propose the integration of suppliers in a central state in Mexico - Antonio Oswaldo Ortega-Reyes; Eva Selene Hernández Gress; Carlos Robles-Acosta (Administrative Sciences, 2018)
This paper addresses the situation of an industrial park in Mexico from the perspective of its community. It exposes a case study approach with the points of view of residents, businesses, and authorities to improve the socioeconomic conditions of the region: Sahagun, Hidalgo. The result of this article comes from a project ran by the Ministry of Economy of the state, to trigger the development of this area. The background of the topic is presented, its theoretical basis, and the methodological design. Finally, an integrative model is exposed to show the necessary actions to articulate enterprises-the society and the government to develop the town.
Keywords: 350; integrative model; enterprise; society; government; development; industrial park